Navigating the dual role of smartphones in e-work: enhancing productivity while managing distractions - Beno, Michal; Caganova, Dagmar (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
Technological progress has made smartphones more than just a communication tool. Nowadays, there are ways to work remotely using a smartphone. Digital advancement and COVID-19 were global milestones for the culture of digital transformation and led to more flexibility and mobility in the workplace. This research aims to study the real experience of smartphone workers. Focus is paid to the e-workforce, comprised of jobholders with work flexibility experience who have formed different post-pandemic standards. Six workers led qualitative examinations from Austria to collect unprocessed data for this study. As reported by these results, working from home via a smartphone 'works'. But there are many factors to consider. Notably, smartphones are a vital piece of equipment for respondents in finishing tasks, but while smartphones offer substantial advantages, using them at home for work is not without challenges. These devices can become an unwelcome distraction at the very least and a legal and operational risk at worst. Smartphones increase mobility and flexibility, as well as the flow of workplace communication, but they also cause distractions in the workplace.